Encephaloduroateriosynangiosis versus conservative treatment for patients with moyamoya disease at late Suzuki stage. (April 2018) - Ge, Peicong; Ye, Xun; Zhang, Qian; Zhang, Dong; Wang, Shuo; Zhao, Jizong
Highlights: The Kaplan-Meier curve of stroke incidence was not statistically significant between the surgical and conservative group. The perfusion improvement in indirect bypass treated patients was higher than in those conservative treated patients. Indirect bypass surgery failed to reduce the risk of recurrent stroke compared to conservative treatment. Abstract: The purpose of this study is to investigate the long-term outcomes after conservative and encephaloduroateriosynangiosis procedures for patients with moyamoya disease at late Suzuki stage. We retrospectively reviewed 64 patients (128 hemispheres) with moyamoya disease at late Suzuki Stage at Beijing Tiantan Hospital. Clinical features, radiologic findings, and outcomes were analyzed. The mean age at diagnosis was 29.0 ± 14.9 years. The distribution of the initial Suzuki stage of MMD was as follows: stage 4, n = 75; stage 5, n = 46; stage 6, n = 7, PCA involvement was observed in 4 (37.5%) hemispheres. The incidence of postoperative stroke was 6.7%. During the average follow-up of 46.9 ± 21.1 months, including postoperative and follow-up strokes, seven of 75 (9.3%) conservatively treated hemispheres and 10 of 87 (10.1%) surgically treated patients experienced a stroke event there was not statistically significant in the Kaplan-Meier curve of stroke incidence between the surgical group and conservative group (log-rank test, p = .848). However, the rate of perfusion improvement in indirect bypass surgically treated patients was higher than in those conservative treated patients 3 months after discharge (p < .05). Although indirect bypass surgery was shown to be effective in improving the cerebral perfusion in patients with MMD at late Suzuki stage, it failed to reduce the risk of recurrent stroke compared to conservative treatment. Further study is needed to determine whether direct bypass surgery is effective in MMD patients at late Suzuki stage.